The Presence and Figures of the Others in Democritus’ Ethics - Motte, André (Peitho. Examina Antiqua, 2017)
Euthymia, the founding concept of Democritus’ ethics, is a thing of the soul, as he says himself, an intimate, eminently personal happiness. What place is given, then, to other individuals in this ethics? Can one be happy without the others? In order to answer these two questions the present paper examines the relevant utterances in which references to the others appear and concludes that despite a clear depreciation of the conjugal bond an altruistic dimension is very strong in this ethics and that several important ideas lie behind this concept.